The Role of Art in the Liminal Setting of Nakivale Refugee Settlement, Uganda - Mateusz Krawczk; Ana Beatriz Baselice Pelicioni (Refuge)
In this article, we examine the role of art in negotiating hybrid identities among refugees in the Nakivale settlement, Uganda. We highlight how refugees use artistic expression to navigate their sense of belonging and reconstruct their lives amid prolonged displacement. Our study explores the dynamic interplay between refugees’ cultural practices and the influences of governmental and non-governmental organizations. By emphasizing the potential of bottom-up artistic initiatives, we challenge traditional views of refugee passivity and underscore the importance of supporting refugee-led cultural expressions to enhance policy-making and improve the quality of life for displaced individuals.